Is “Meaningfulness” a General Mediating Factor? The Salutogenic Revolution of Question-Setting in Health Science and Occupational Psychology - Varga, Károly; Tóth, Ákos; Roznár, József; Oláh, András; Betlehem, József; Jeges, Sára (European Journal of Mental Health, 2012)
According to our earlier researches – stating that on the one hand in the career competency of the examined subjects, out of the Core Job Dimensions present in the Hackman-Oldham Job Characteristic Model, only Meaningfulness (task significance) contributed significantly to inducing favourable Personal and Work Outcomes, and on the other hand, among the components of the Sense of Coherence, portrayed as a health and well-being factor in Antonovsky’s Salutogenic Model, it was Meaningfulness that had a preeminent role – we asked the question: to what extent can this positive effect of Meaningfulness be further generalized? That is, regarding women in Hungary who choose a healthcare career, whether Meaningfulness felt within their job motivates them with a significant enough force to be a counter-effective factor to job abandonment (especially frequent in Hungary), to persevere despite the difficult circumstances. From a methodical point of view, we completed a quasi-case study in the circle of 158 female students taking healthcare courses and 79 women working in healthcare for at least five years. As control groups we used the age- and sex-standardized random samples of non-healthcare students as well as workers. Here, Meaningfulness within the Sense of Coherence proved to be the significant factor for staying in the healthcare profession. Practical conclusion of the research: during the training in healthcare courses, an emphasis has to be laid upon developing the Sense of Meaningfulness in the person, by means of establishing life-career models, personal career design, and creating the chances of a healthier lifestyle.